2017
DOI: 10.1111/scs.12521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational intervention for district nurses about preparedness to encounter women exposed to intimate partner violence

Abstract: The results indicate that the intervention had a low impact on district nurses' preparedness. The educational intervention must be adjusted; a main focus of changes should be the addition of continuing postintervention supervision and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…These should also lead groups not only of women, but also of men, focusing on gender reflection and empowerment based on community interventions to break out of abusive relationships. 12,27 Professional training is essential in order to promote care for women who experience a marital daily life permeated by violence, as indicated by a national research conducted in Santa Catarina with Family Health Strategy (FHS) doctors and nurses. These refer to the unpreparedness in how to act 8/11 in this context, signaling the need for a management that prioritizes this problem recognition and a qualified attention to these women, which involves, among other issues, knowledge about the resources of empowerment.…”
Section: /11mentioning
confidence: 99%
See 1 more Smart Citation
“…These should also lead groups not only of women, but also of men, focusing on gender reflection and empowerment based on community interventions to break out of abusive relationships. 12,27 Professional training is essential in order to promote care for women who experience a marital daily life permeated by violence, as indicated by a national research conducted in Santa Catarina with Family Health Strategy (FHS) doctors and nurses. These refer to the unpreparedness in how to act 8/11 in this context, signaling the need for a management that prioritizes this problem recognition and a qualified attention to these women, which involves, among other issues, knowledge about the resources of empowerment.…”
Section: /11mentioning
confidence: 99%
“…11 A study conducted in Sweden reveals that Primary Health Care (PHC) nurses realize the limitations of women in breaking up violent relationships. 12 Considering long years of permanence in marital relationship permeated by violence and the difficulties in getting out of this harmful cycle to their physical and mental health, the following was delineated as the research question: what resources favor women to cope with marital violence? The objective was to unveil the strategies used by women to cope with marital violence.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have suggested that IPV should be a part of the nursing curriculum (Alhalal, 2020 ), and that educating professionals on this topic is needed (Williams et al, 2017 ). Others have indicated that formal education is insufficient (Sundborg et al, 2018 ; Yeung et al, 2012 ); in order to feel confident in talking about IPV, health care staff need training and experience (Yeung et al, 2012 ) as well as continuous supervision and support (Sundborg et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physical space of the network facilities often does not allow a welcoming environment, which inhibits the sharing of intimate issues between the client and the professional. Added to this fact is the limitation in the number of professionals, a reality that affects the unavailability of care with women or work overload for the worker, as pointed out by studies developed in Brazil, Sweden and Saudi Arabia (8,(13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the demand for care in health services emerges from illness (6) . Studies conducted in Brazil and Sweden recognize that, for being closer to women in situations of marital violence, professionals working in Primary Health Care (PHC) should be prepared to embrace and direct women who experience violence perpetrated by their intimate partner to restore health and break abusive relationships (8)(9) .…”
Section: Introductionmentioning
confidence: 99%